1998
DOI: 10.1007/s100480050053
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Caenorhabditis elegans dystrophin-like gene dys-1 lead to hyperactivity and suggest a link with cholinergic transmission

Abstract: Mutations in the human dystrophin gene cause Duchenne muscular dystrophy, a common neuromuscular disease leading to a progressive necrosis of muscle cells. The etiology of this necrosis has not been clearly established, and the cellular function of the dystrophin protein is still unknown. We report here the identification of a dystrophin-like gene (named dys-1) in the nematode Caenorhabditis elegans. Loss-of-function mutations of the dys-1 gene make animals hyperactive and slightly hypercontracted. Surprisingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
136
1
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(153 citation statements)
references
References 28 publications
15
136
1
1
Order By: Relevance
“…dys-1 mutants develop a peculiar phenotype consisting of hyperactivity, exaggerated head bending and a tendency to hypercontract (Bessou et al, 1998). These mutants undergo only slight muscle degeneration (Bessou et al, 1998;Grisoni et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…dys-1 mutants develop a peculiar phenotype consisting of hyperactivity, exaggerated head bending and a tendency to hypercontract (Bessou et al, 1998). These mutants undergo only slight muscle degeneration (Bessou et al, 1998;Grisoni et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These mutants undergo only slight muscle degeneration (Bessou et al, 1998;Grisoni et al, 2003). However, in a sensitized hlh-1(cc561) background, which is a mild mutation of the C. elegans homologue of the myogenic factor MyoD, dys-1 mutations lead to an extensive time-dependent muscle degeneration (Gieseler et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…2 To our surprise, null mutations of the so-called dys-1 gene left the C. elegans muscles almost unaffected, but resulted in hyperactivity and a tendency to hypercontract. Moreover, the dys-1 mutants were hypersensitive to Ach and to the drug aldicarb, which is used in C. elegans as an indirect measurement of cholinergic activity.…”
mentioning
confidence: 90%
“…The most straightforward interpretation of this phenotype was -and remainsthat the absence of dystrophin upregulates cholinergic transmission in C. elegans. 2 It was later shown that acetylcholinesterase (AchE) activity was slightly reduced in dys-1 mutants. 3 However, since dys-1 and AchE mutants have different phenotypes in C. elegans, it was clear that additional directions had to be explored to explain the dys-1 phenotype.…”
mentioning
confidence: 99%
“…2 In addition, loss-of-function mutations of the C. elegans dystrophin-1 gene confirmed the role of human dystrophin in the manifestation of the neuromuscular disease of Duchenne. 3 During the last years a novel invertebrate model system has emerged: sponges (phylum Porifera), which are among the earliest-branching nonbilaterian animals. 4 Recent biomarker analyses date the occurrence of probable stem-group poriferans back before the end of the Marinoan glaciation (B635 Myr ago) 5 and molecular clock analyses estimated that the main poriferan lineages diverged in the Cryogenian/ Ediacaran, 6 well before the rapid appearance of major metazoan groups (Cambrian Explosion).…”
mentioning
confidence: 99%